Mitigating peak pressure of storm geysering by orifice plates installed at the top of vent pipes - Huang, Biao (Water science and technology : a journal of the International Association on Water Pollution Research, 2018)
Large air pockets can be trapped in storm sewer systems during intense rain events. Uncontrolled release of these air pockets may cause geysering and pressure surges, resulting in flooding, pipe failures and safety issues. Thus, there is a great need to develop methods to retrofit existing sewer systems and to provide guidance on system design. A large-scale physical model was established to evaluate air-control orifice plates in reducing geysering intensity by utilizing air cushion effects over the process of air escape. Experimental results indicate that the magnitude of pressure fluctuations can be reduced significantly with partially open vent pipes. The maximum pressure head can be reduced by approximately two-thirds, and the magnitude of relative pressure oscillation decreased by about 95% when the diameter ratio of the air-control orifice to the vent pipe is below 25%. Air-water mixture jets can be avoided in such cases. The effect of using multiple vent pipes with orifice plates was also evaluated and found to be effective. Thus, air-control vent pipes can be applied to alleviate geysering and related pressure transients